Uso de bacteriófagos no biocontrole de Salmonella entérica - Passos, Aline Catarina Santos dos (2022)
A Salmonella spp. it is one of the main microorganisms involved in foodborne diseases, which makes it necessary to take measures for its elimination in the food industry. In view of this approach, bacteriophages (phages), which are viruses that infect prokaryotes, are gaining space in several areas, mainly in the food industries, as they present themselves as an advantageous biological control of bacteria, without leaving traces of substances, consequently making them - an excellent control alternative. When associated with polymers, in addition to protection, they can provide a gradual release acting for longer periods, allowing a controlled release of the substance in the area of operation. Thinking about this technology, the objective of the present study was to develop an innovative product for the biological control of different Salmonella enterica serovars, through the preparation of a cocktail of bacteriophages, formulated in extended release adhesive biocompressed tablets, in order to be needed in drinking water. cooling tanks for chicken slaughter. The biocompresses were prepared with 30% Polyox WSR-303, 7,000,000 g / mol, 69% ethylene polyoxide, 100,000 g / mol, and 1% pool of lyophilized bacteriophages, prepared by direct direct compression in a eccentric compression. Its efficiency was tested by mimicking the real conditions of the cooling process of chicken carcasses, divided into four treatments, where T1 - positive control, T2 - negative control, T3 - low concentration phage biocompressants [2.7x103 CFU / mL] Salmonella enterica and T4 - Phage biocompressants with high concentration [2.7x106 CFU / mL] of Salmonella enterica. The results attenuated that there was a reduction in pathogens, but there was no difference between treatments, thus, it is concluded that biocompresses are not significantly differentiated in the release of bacteriophages for action against Salmonella enterica.